البحث عن المعلومات وأثره على اقتناء المعرفة : دراسة تجریبیة - هویه مصبح فرحان العازمى (المجلة الدولية لعلوم المكتبات والمعلومات)
his study focuses on clarifying the different ways in which students gainknowledge and influence their behavior in the search for information and thustheir knowledge acquisition, especially in the field of libraries. The forms ofresearch behavior of students and their acquisition of knowledge, and exploringnew ways of teaching, which in turn affect the nature of their behavior in thesearch for sources of information, which leads to reduce the failure of the processof knowledge acquisition.In this context, the study was conducted on a sample of pre-graduatestudents whose objective is to verify this by selecting a course from the curriculaof the library and information department in the Faculty of Education in theGeneral Authority for Applied Education in Kuwait. In the method of teaching thecourse to measure the impact of this on the behavior of students in the researchand acquisition of information.